Aesthetic outcome following breast‐conserving surgery assessed by three evaluation modalities in relation to health‐related quality of life. Issue 1 (30th August 2018) - Dahlbäck, C.; Ringberg, A.; Manjer, J.
Abstract : Background: The aim of this study was to compare the agreement between three different methods for evaluation of aesthetic outcome following breast‐conserving surgery and adjuvant radiotherapy: a patient questionnaire, panel evaluation of photographs and the software BCCT.core. A further aim was to examine how these modalities predict health‐related quality of life as measured by the validated Breast‐Q™ questionnaire. Methods: At 1‐year follow‐up after breast‐conserving surgery, patients completed a study‐specific questionnaire. Postoperative photographs were evaluated using the software BCCT.core. A panel of three healthcare professionals assessed preoperative and postoperative photographs. Agreement between methods was assessed using Spearman's correlation coefficients ( r s ). The Breast‐Q™ questionnaire was sent to study participants. The ability of the different evaluation methods to predict Q‐scores for the health‐related quality‐of‐life (HRQoL) domains satisfaction with breasts and psychosocial well‐being was investigated using receiver operating characteristic (ROC) curves. Results: A total of 532 patients undergoing breast‐conserving surgery were examined before surgery. At 1‐year follow‐up, 334 patients completed the study‐specific questionnaire. Postoperative photographs from 310 patients were evaluated using BCCT.core. The panel of healthcare professionals assessed photographs from 215 patients. Agreement between the different evaluation modalities was poor. The strongest agreement was noted between the panel evaluation for symmetry and BCCT.core results ( r s  = 0·59, P  < 0·001). The Breast‐Q™ questionnaire was returned by 348 patients. Patient satisfaction ratings at 1‐year follow‐up best predicted long‐term HRQoL measured using the Breast‐Q score, both in terms of satisfaction with breasts (area under the curve (AUC) 0·80, P  < 0·001) and psychosocial well‐being (AUC 0·73, P  < 0·001). Conclusion: There is currently no ideal method for evaluating aesthetic outcome after breast‐conserving surgery and adjuvant radiotherapy. These results emphasize the use of patient‐related outcome measures. Abstract : Better methods needed